2019
DOI: 10.1002/yea.3397
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and antifungal susceptibility of microsatellite genotypes of Candida albicans from superficial and deep locations

Abstract: A set of 185 strains of Candida albicans from patients with vulvovaginal candidiasis (VVC) and from non‐VVC clinical sources in southwest China was analysed. Strains were subjected to genotyping using CAI microsatellite typing and amplification of an intron‐containing region of the 25S rRNA gene. Microsatellite genotypes of strains from non‐VVC sources showed high polymorphism, whereas those of VVC were dominated by few, closely similar genotypes. However, among non‐VVC strains, two genotypes were particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…In this study, we tested 238 C. albicans isolates (120 blood, 60 oral, 28 body fluid and 29 superficial isolates) and obtained 73 CAI genotypes (49 CAI genotypes in blood, 25 in oral, 19 in body fluids and 18 in superficial isolates). Unlike C. albicans obtained from women with vulvovaginal candidiasis in China, the strains in this study from extragenital sites showed higher diversity 26,36 . The most common genotype was not representative of most strains.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In this study, we tested 238 C. albicans isolates (120 blood, 60 oral, 28 body fluid and 29 superficial isolates) and obtained 73 CAI genotypes (49 CAI genotypes in blood, 25 in oral, 19 in body fluids and 18 in superficial isolates). Unlike C. albicans obtained from women with vulvovaginal candidiasis in China, the strains in this study from extragenital sites showed higher diversity 26,36 . The most common genotype was not representative of most strains.…”
Section: Discussioncontrasting
confidence: 62%
“…Unlike C. albicans obtained from women with vulvovaginal candidiasis in China, the strains in this study from extragenital sites showed higher diversity. 26,36 The most common genotype was not representative of most strains. Interestingly, TA B L E 2 CAI groups and in vitro antifungal susceptibility strains from different sites in this study shared identical or at least very similar CAI genotypes, which is consistent with the theory that invasive candidiasis originates from the endogenous microbiota.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The genotype distribution of C. albicans strains has been associated with different clinical conditions of VVC (4,5). The genotypic differences of C. albicans strains retrieved from VVC patients and healthy women reveal that VVC-linked strains possess specific genotypes (6). Hence, studying the genotypes of different subspecies of C. albicans strains will contribute to understanding their pathogenic mechanisms, which is important for increasing the recovery rate and controlling the infection rate.…”
Section: Introductionmentioning
confidence: 99%